Peran Pemerintah Desa Dalam Meningkatkan Potensi Pertanian Desa Di Desa Mampang Kecamatan Kotapinang Kabupaten Labuhanbatu Selatan - Tarigan, Imelda; Sembiring, Walid Musthafa; Angelia, Nina (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2024)
Mampang is one of the villages in Kotapinang, South Labuhanbatu Regency, North Sumatra which has considerable agricultural potential. The potential of Mampang Village is oil palm, rubber and rice. However, agriculture in Mampang Village has not progressed very rapidly. This is due to the lack of Human Resources and the lack of attention from the Village Government. Therefore, the authors conducted research on the role of the village government in increasing agricultural yields in Mampang Village. The theory used in this study is the role theory of Soekanto Sulistyowati (2017: 211), this study uses a qualitative descriptive method through interview, observation and documentation techniques. This study consisted of main informants, key informants and additional informants. The results of this study indicate that the role of the village government is not good enough in increasing the potential of village agriculture. increase the potential of rural agriculture.